Physicochemical and chromatographic method of characterization of Matricaria recutita tinctures - García Barrantes, Pedro M. (2016)
The pharmacological activity of medicinal products containing plant materials depends on their specific components. However, these components are not characterized in their entirety in all cases. Therefore, manufacturing processes must be duly characterized and validated. Aims: To characterize a chamomile (Matricaria recutita) tincture through chemometric analysis of chromatographic data in order to establish quality parameters for its production. Methods: Various chamomile tinctures were manufactured and the precision and robustness of the production process for each was verified. The physicochemical properties of the tinctures were characterized and their chromatographic digital fingerprints analysed through chemometric methods. Results: A good correlation between the physicochemical characterization and the chromatographic analysis was demonstrated. The preparation methodology was proved to be repeatable as long as the source of the plant material is not altered. Conclusions: The principal component multivariate analysis of chromatograms was a helpful and simple tool for the characterization and traceability of the production method.